2020
DOI: 10.47653/farm.v7i1.159
|View full text |Cite
|
Sign up to set email alerts
|

UJI EFEKTIVITAS GEL EKSTRAK ETANOL 96% DAUN SINGKONG (Manihot esculenta Crantz.) PADA PENYEMBUHAN LUKA SAYAT KELINCI JANTAN GALUR New Zealand White

Abstract: Daun singkong (Manihot esculenta Crantz.) memiliki kandungan flavonoid, tanin serta saponin yang terbukti berkhasiat sebagai obat untuk mempercepat proses penyembuhan luka. Penelitian ini bertujuan untuk membuat formulasi gel dari ekstrak daun singkong dan uji efektivitas dalam penyembuhan luka sayat pada kelinci jantan. Jenis penelitian ini adalah eksperimental dengan cara membuat gel ekstrak daun singkong yang akan diujikan pada hewan uji sebanyak 4 ekor dengan 6 kelompok perlakuan. Data penyembuhan luka dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…Tannins can affect wound healing with several cellular mechanisms, including increasing the reformation of dermis tissue in wound tissue (fibroplasia) (Negara, 2014). in research (Megawati et al, 2020), showed that the results of statistical tests had a significant effect on wound healing in male rabbits and showed that ethanol extract with a concentration of 60% had the best effect in accelerating the healing process of cuts.…”
Section: Resultsmentioning
confidence: 99%
“…Tannins can affect wound healing with several cellular mechanisms, including increasing the reformation of dermis tissue in wound tissue (fibroplasia) (Negara, 2014). in research (Megawati et al, 2020), showed that the results of statistical tests had a significant effect on wound healing in male rabbits and showed that ethanol extract with a concentration of 60% had the best effect in accelerating the healing process of cuts.…”
Section: Resultsmentioning
confidence: 99%
“…The parameter in this study is to see a decrease length of wound, and time of disappearance of erythema. Length measurement healing for cuts, namely using caliper for 14 days (Megawati et al, 2020). The data to be analyzed namely The percentage of wound healing is obtained through measurement length of the incision.…”
Section: Wound Healing Percentagementioning
confidence: 99%
“…The derived ethanol extract of green algae (EEGA) was made into gels using three formulations, as shown in Table 1 (Megawati et al, 2020).…”
Section: Gel Formulation and Preparationmentioning
confidence: 99%
“…Triethanolamine was chosen to provide an alkaline atmosphere to the carbomer so that the gel becomes thick and clear (Septiawan, 2012). Finally, the gel base was added with the EEGA gradually in small amounts while stirred until homogeneous and then placed in a gel container (Megawati et al, 2020).…”
Section: Componentsmentioning
confidence: 99%